From the Archives of Levon Mkrtchyan. M.S.Petrovikh as the Editor of Russian Editions of Armenian Poetry - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The eminent Russian poetess Maria Petrovikh was not only a talented translator of many Armenian poets, but also editor of several editions of their works translated into Russian. The poetic volume of H.Tumanian (1969), the collection “Armenian Medieval Poetry” (1971),“The Anthology of Armenian Poetry” (in two volumes, 1973), Grigor Narekatsi‘s “The Book of Sadness” (translated by N.Grebnev, 1977) were published under her edition. The archive materials, especially letters witness the devoted detailed work of M.Petrovikh as an editor.
Keywords: archive, Armenian poetry, Russian translation, publication, editing